Prevalence of nocturnal enuresis and its influence on quality of life in school-aged children. Issue 3 (June 2016) - Sarici, Hasmet; Telli, Onur; Ozgur, Berat Cem; Demirbas, Arif; Ozgur, Senem; Karagoz, Mehmet Ali
Summary: Objective: According to the ICCS definitions, enuresis is defined by an intermittent, wetting during sleep after organic causes have been ruled out with a minimum wetting frequency of once per month. Previous studies reported a prevalence rate of 9–12%. Eighty to 90% of enuresis cases are identified as primary enuresis and are based on genetic predisposition, biological and developmental factors. On the other hand, secondary enuresis frequently arises from psychological factors. In this study we aimed to determine the prevalence and associated factors of nocturnal enuresis (NE) among primary school children. Method: We initiated a prospective cross-sectional epidemiological study from January 2013 to May 2013 by sending a questionnaire to parents of 4250 school children, aged 6–13 years. The questionnaire consisted of three parts. The first part investigated the demographic characteristics of the child and family, such as age, gender, number of siblings, and enuresis history of the parents and siblings. The second part consisted of questions about the presence and frequency of bedwetting, presence of constipation/fecal incontinence, and presence of daytime incontinence (DI). The last part surveyed school performance and the effect of enuresis on quality of life of parents and children. Logistic regression analyses were conducted to determine the significant predictive factors for NE. Results: The overall prevalence of enuresis was 9.52%. The prevalence of NE among boys and girls was 12.4% and 6.5%, respectively. Daytime incontinence was present in 18% of children. Of enuretic children, 59.2% had a positive family history of enuresis. Constipation was found in 13.2% of children with enuresis and there was no significant association between NE and the presence of constipation. In addition, 48% of enuretic children had poor school performance. Conclusions: The current study demonstrated that age, male gender, parents' history of enuresis, and siblings' history of enuresis were significant predictive factors for NE. The majority of the parents did not have adequate interest in enuretic children and most of the children were not treated. Physicians should inform parents of enuretic children with the aim of solving this problem to prevent future issues and development of adulthood lower urinary tract symptoms (LUTS).